PENERAPAN MODEL PROBLEM BASED INSTRUCTION (PBI) DISERTAI PERFORMANCE ASSESSMENT UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWAKELAS VIII A PADA SUB POKOK BAHASAN LUAS PERMUKAAN DAN VOLUME KUBUS DAN BALOK DI SMP NEGERI 1 JENGGAWAH - Puspitasari, Erina Tri; Susanto, S; Trapsilasiwi, Dinawati (Department of Mathematics Education , University of Jember, 2014)
Abstract.The aims of this study was: (1) to explain the implementing of PBI (Problem Based Instruction) models with Performance Assessment in the surface area and volume of cube and beamsat VIII-A Class of Junior High School 1 Jenggawah Jember at even semester of 2012/2013 academic years; (2) to analyze students’ activities during teaching learning process by using of PBI (Problem Based Instruction) models with Performance Assessment; (3) to analyze the result of students’ achievement after implementing of PBI (Problem Based Instruction) models with Performance.The research design used Classroom Action Research (CAR).The research subject was 37 students in class VIII-A of SMP Negeri 1 Jenggawah. Data collection method was observation, interview, test, and documentation.In the first cycle, completeness the student learning outcomes classically is 59,46%. And the second cycle, completeness the student learning outcomes classically is 89,19%. So the increase of the both cycle classically above was 30,37%. KeyWords:problem based instruction, performance assessment, classroom action research